Diffuse Large B-Cell Lymphoma of the Mandible Diagnosed by Metagenomic Sequencing: A Case Report - Liu, Kaili; Gao, Yang; Han, Jiawei; Han, Xu; Shi, Yingqi; Liu, Chao; Li, Jie (Frontiers in Medicine, 2021)
Introduction: Non-Hodgkin lymphoma (NHL) has a much higher incidence rate than Hodgkin lymphoma. Approximately 40% NHL occurs in extranodal tissues or organs, and its clinical manifestations are often nonspecific. Primary bone NHL involving the mandible is an uncommon NHL that is characterized by fever, gum swelling and toothache. Therefore, it is often misdiagnosed as oral diseases. Case Presentation: A 52-year-old female had recurrent fever for more than 1 month, with numbness in her left jaw and toothache. PET/CT showed an uptake area in the left mandible, suggesting microbial infections. However, antibacterial, and antiviral treatment were ineffective. Furthermore, metagenomic sequencing of plasma reported no pathogens, but instead showed significant copy number variations of multiple chromosomes, which highly suggested the existence of tumor. Finally, diffuse large B-cell lymphoma (DLBCL) was diagnosed by mandibular biopsy, and the patient was transferred to Hematology department for chemotherapy. Conclusion: mNGS not only assists rapid etiological diagnosis, but also helps rule out infection and diagnose malignant neoplasm.